KUIS TESL Trainee Teachers’ Readiness in Integrating Naqli and Aqli Knowledge in English Class - Norshilawani Shahidan; Natasha Ariffin; Suhana Mohamed Lip; Suziana Hanini Sulaiman; Shazarina Zdainal Abidin (International Islamic Schools Alliance, 2021)
Numerous researches have been conducted in relation to knowledge integration in the teaching and learning process especially related to Science and Islamic education. However, only few studies have researched on the integration of naqli knowledge in English classes. Due to that, this study is proposed to research on readiness to apply knowledge integration in English class. This study will be conducted on Teaching English as a Second Language (TESL) trainee teacher’s from Kolej Universiti Islam Antarabangsa Selangor (KUIS) to find out their level of readiness to integrate naqli and aqli knowledge in English class. This study will apply quantitative method of data collection by using questionnaires to gather the data. This study is as an attempt to investigate the issue of knowledge integration in Malaysian context which is hoped will lead to the improvement of the quality of TESL trainee teachers particularly in KUIS.